Social camouflaging predicts eating disorder symptomatology among female patients with Borderline Personality Disorder - Carpita, Barbara; Nardi, Benedetta; Giovannoni, Federico; Parri, Francesca; Pronestì, Cristiana; Bonelli, Chiara; Massimetti, Gabriele; Pini, Stefano; Bruno, Antonio; Muscatello, Maria Rosaria Anna; Della Rocca, Bianca; Fiorillo, Andrea; et al. (Frontiers in Psychiatry, 2025)
BackgroundBorderline Personality Disorder (BPD) frequently co-occurs with both eating disorders (EDs) and elevated autistic traits, particularly among women. Social camouflaging—a set of strategies used to mask neurodivergent behaviors—has been extensively studied in autism spectrum conditions but remains underexplored in BPD populations. Given emerging evidence linking camouflaging behaviors to disordered eating, this study aimed to investigate the relationship between social camouflaging and eating disorder symptomatology in women with BPD.MethodsA total of 110 female participants (64 with BPD, 46 healthy controls) were assessed using the Camouflaging Autistic Traits Questionnaire (CAT-Q), the Eating Disorder Inventory-2 (EDI-2), and the Adult Autism Subthreshold Spectrum (AdAS Spectrum).ResultsWomen with BPD scored significantly higher on all domains of the CAT-Q, AdAS Spectrum, and EDI-2. Significant correlations emerged between CAT-Q and EDI-2 scores. CAT-Q total score and CAT-Q compensation domain significantly predicted EDI-2 total score.ConclusionSocial camouflaging is significantly elevated in women with BPD and is closely associated with disordered eating symptoms. Findings highlight camouflaging as a potential transdiagnostic mechanism linking autistic traits and ED symptomatology in BPD populations, with implications for diagnostic clarity and personalized treatment strategies.